The Influence of Education, Consumer Awareness, and Government Regulation on Sustainable Consumption Behavior: A Case Study on Ciawitali Market in Garut Regency - Hasibuan, Faisal Umardani; Judijanto, Loso (Westscience Press, 2023)
The present study examines the complex relationship that exists among education, consumer consciousness, governmental oversight, and sustainable consumption practices in the vicinity of Ciawitali Market, Garut Regency. Insights regarding the demographic profiles, educational attainment, consumer awareness, perception of government regulation, and sustainable consumption behavior of 195 participants were obtained from the sample. The relationships between these variables were analyzed utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS). Positive correlations were found between education and sustainable consumption behavior, consumer awareness and sustainable consumption, and government regulation and both consumer awareness and sustainable consumption behavior, according to the findings. The model demonstrated a strong correspondence with the data, underscoring the importance of effective government regulations, consumer education, and consumer awareness in promoting sustainable practices. By utilizing these insights, policymakers, educators, and market stakeholders can effectively develop focused interventions that promote sustainable development in the Ciawitali Market.